Pengaruh Kecerdasan Emosional, Kepemimpinan Transformasional, dan Keterikatan Kerja Terhadap Kepuasan Kerja Pegawai Pada Badan Pendapatan Daerah Kota Batam - Ahmad Ismail; Rommy Wijaya; Hendri Herman; Sudianto Sudianto (eScience Humanity Journal, 2025)
This study aims to examine the influence of emotional intelligence, transformational leadership, and work engagement on employee job satisfaction at the Regional Revenue Agency of Batam City, Indonesia. Employee job satisfaction is a critical factor in improving organizational performance, particularly in public sector institutions that face high administrative demands and service responsibilities. This research adopts a quantitative approach using a causal associative design. The population consisted of all civil servants working at the Regional Revenue Agency of Batam City, totaling 67 employees, and a saturated sampling technique was applied, resulting in 67 respondents. Data were collected through structured questionnaires measured using a Likert scale and analyzed using multiple linear regression with SPSS software. The results of the study indicate that emotional intelligence has a positive and significant effect on employee job satisfaction. Employees with higher emotional intelligence are better able to manage work pressure, maintain interpersonal relationships, and adapt to organizational demands. Transformational leadership was also found to have a significant positive effect on job satisfaction, highlighting the importance of inspirational motivation, individual consideration, and intellectual stimulation in enhancing employees’ positive attitudes toward their work. Furthermore, work engagement significantly influences job satisfaction, as employees who demonstrate vigor, dedication, and absorption tend to experience higher levels of satisfaction in their jobs. Simultaneously, emotional intelligence, transformational leadership, and work engagement have a significant combined effect on employee job satisfaction, with an adjusted R-square value of 0.989. This indicates that 98.9% of the variation in job satisfaction can be explained by these three variables, while the remaining 1.1% is influenced by other factors not examined in this study. The findings suggest that public organizations should prioritize the development of emotional intelligence, effective transformational leadership practices, and employee engagement to enhance job satisfaction and organizational performance.